Psychological impacts among diabetic amputee patients in Tengku Ampuan Afzan Hospital, Kuantan - Mohd Adnan, Mohd Jazlan; Sulong, Ahmad Fadzli; Mohd Yusof, Nazri; Che Ahmad, Aminudin (2014)
Background Literature review on diabetic foot problem in Malaysia so far has mainly report on epidemiology and complication related to diabetic foot problems. To date, there were no local study that investigates the psychological aspect and the quality of life among patients with diabetic foot problems. .